AGR218: Basic Agricultural Engineering / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (Universiti Teknologi MARA (UiTM), 2017)
This in an introductory course on farm mechanization. Student will explain the construction and operation of various engine system, operate farm tractor mounted with various implements and explain the importance of maintenance.